ANALYZING THE INFLUENCE OF ESG SCORES ON FINANCIAL PERFORMANCE OF THE COMPANIES: A CRITICAL STUDY - Verma, Jyotika; Singel, Rashmi; Nangia, Richa; Prakash, Anshika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Globally, one can find a growing need on business organisations to take social responsibility seriously. The financial performance of a firm is closely linked to its information disclosure of ESG operations, and this is being scrutinised by a wider range of stakeholders because of the inconsistent findings of current research. These stakeholders include consumers, workers, communities, regulators, and investors. In light of the lack of an integrated analytical framework worldwide that particularly assists businesses in developing indices and indicators that gauge an enterprise's sustainability. Thus, the company's management processes and code of ethics can have an impact on the primary factors that determine the quality of ESG reporting and later it’s scoring. Sustainable finance can be found to be highly beneficial in scaling up the field and so promoting the achievement of significant objectives such as the UN Sustainable Development Goals and the Paris Agreement. This study looks at the linkage between ESG factors and Financial Performance of the companies.